Hochschild cohomology of incidence algebras as one-point extensions - Gatica, María Andrea (2003)
The aim of this paper is to compute the Hochschild cohomology groups of particular of algebras associated to partially ordered sets. © 2003 Elsevier Science Inc. All rights reserved.